Sociocultural-based games enhancing manipulative movement skills in Indonesian kindergartens - Nur Sita Utami; Joko Nurkamto; Mohammad Furqon Hidayatullah; Hari Yuliarto (LPMPP Universitas Negeri Yogyakarta, 2025)
This study aims to analyze the influence of a sociocultural-based manipulative movement game model on the manipulative movement skills in children aged 5–6 years. A quasi-experimental design was employed, using a pretest-posttest control group approach. A total of 24 students were purposively selected with prior written consent from their parents or guardians. The experimental group (n = 12) consisted of students from TK Negeri 4 Yogyakarta, while the control group (n = 12) came from TK Negeri 11 Yogyakarta. The intervention involved a manipulative movement game model developed based on Vygotsky’s sociocultural perspective, integrating four elements of physical literacy from the Australian Physical Literacy Framework: manipulative movement skills, confidence, collaboration, and rule comprehension. Manipulative movement skills were assessed using the ball skills subdomain of the Test of Gross Motor Development–3 (TGMD-3). Data were analyzed using the Mann–Whitney U test and the Wilcoxon rank-sum test. The results revealed significant differences between the pretest and posttest groups (W = 56.949, p = 0.04384) and between the control and experimental groups in the posttest (W = 44.807, p = 0.0004301). These findings indicate that the developed model effectively enhances children's manipulative movement skills. The study underscores the importance of integrating the principles of mediated learning, scaffolding, and the zone of proximal development into early childhood physical-motor learning. The implementation of this model is recommended as an alternative approach to physical-motor learning in Indonesian kindergartens.